Decision-Making for Destination Therapy Left Ventricular Assist Devices. (March 2015) - McIlvennan, Colleen K.; Jones, Jacqueline; Allen, Larry A.; Lindenfeld, JoAnn; Swetz, Keith M.; Nowels, Carolyn; Matlock, Daniel D.
<x xml:space="preserve">Abstract</x> Background— Implanting centers often require the identification of a dedicated caregiver before destination therapy left ventricular assist device (DT LVAD) implantation; however, the caregiver experience surrounding this difficult decision is relatively unexplored. Methods and Results— From October 2012 through July 2013, we conducted semistructured, in-depth interviews with caregivers of patients considering DT LVAD. Data were analyzed using a mixed inductive and deductive approach. We interviewed 17 caregivers: 10 caregivers of patients living with DT LVAD, 6 caregivers of patients who had died with DT LVAD, and 1 caregiver of a patient who had declined DT LVAD. The themes identified, which could also be considered dialectical tensions, are broadly interpreted under 3 domains mapping to decision context, process, and outcome: (1) the stark decision context, with tension between hope and reality; (2) the challenging decision process, with tension between wanting loved ones to live and wanting to respect loved ones' wishes; and (3) the downstream decision outcome, with tension between gratitude and burden. Conclusions— Decision-making surrounding DT LVAD should incorporate decision support for patients and caregivers. This should include a focus on caregiver burden and the predictable tensions that caregivers experience.